Doświadczalne Badania Elementów Maszyn Projektowanych Metodą Nośności Granicznej - Kapkowski, J.; Stupnicki, J. (Engineering Transactions, 1973)
The paper contains the description and results of experiments performed by means of the photo-stress method on specimens subject to plane states of stress. The forms of the specimens are determined by the method of load carrying capacity. The process of formation and propagation of plastic zones is analyzed and the load carrying capacity is determined, the latter being compared with the theoretically derived values.